Using Synthetic Chelating Agents to Decrease Phosphorus Binding in Soils. Issue 8 (August 2016) - Edwards, Cristie L.; Maguire, Rory O.; Whitehurst, Garnett B.; Thomason, Wade E.; Alley, Mark M.
Abstract : Abstract: Most acid soils have a high capacity to bind phosphorus (P) strongly on iron (Fe) and aluminum (Al) hydroxides, resulting in low P fertilizer use efficiency. Organic chelating agents form strong bonds with metals in soil and may reduce P binding with Fe and Al and increase fertilizer P use efficiency. Ethylenediamine tetraacetic acid (EDTA), hydroxyethyl ethylenediamine triacetic acid (HEEDTA), gluconic acid, and citric acid were tested to determine their influence on water-soluble P (WSP), Mehlich-1 P, and Mehlich-3 P in a loam and sand fertilized with P and incubated for 49 days. Soil P sorption capacity (PSC) was estimated from an oxalate extraction of Fe and Al, and chelates were applied at rates of 90% of the PSC. EDTA and HEEDTA were also applied at 0, 30, 60, 90, 120, and 150% PSC to produce a rate response curve for WSP in a second soil incubation. The EDTA, HEEDTA, and citric acid significantly ( P < 0.05) reduced P sorption in the loam and sand when measured by WSP. In soils without P fertilizer added, EDTA and HEEDTA resulted in a significant increase in WSP concentrations, as well as increased concentrations of Mehlich-1 P and Mehlich-3 P. With increasing chelation rates of EDTA and HEEDTA, there was a linear increase in WSP for both soils, indicating higher rates were most effective at decreasing P sorption. The application of chelating agents, with and without P fertilizer, could potentially increase plant availability of P, therefore reducing P fertilizer.